ANALISIS RASIO KEUANGAN DALAM MEMPREDIKSI PERUBAHAN LABA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Febriyanto Febriyanto; Riza Setiawan Gusma (Jurnal Ilmu Manajemen Retail Universitas Muhammadiyah Sukabumi, 2021)
Rapid technological developments make the capital market create various opportunities or alternatives for investors. On the other hand, companies seeking funds must compete in obtaining funding from investors. One way for companies to get funding is by issuing and selling company shares to investors on the stock exchange. As with the problem formulation, the purpose of writing this thesis is to provide empirical evidence about the effect of changes in Current Ratio (CR), Debt To Equity Ratio (DER), Gross Profit Margin Ratio (GPM), and Total Asset Turnover Ratio (TAT) in predicting profit changes in automotive sub-sector manufacturing companies for the next one year. The target population of this study is all manufacturing companies listed on the Indonesian stock exchange. The automotive sub-sector and reported in 2018 to June 2020, with purposive sampling technique, the research sample was obtained as many as 12 automotive companies. The data analysis tool used in this research is multiple regression analysis test, classical assumption test, and hypothesis test. Based on the results of research and discussion, the following conclusions can be made about the positive and significant effect of the Current Ratio on changes in earnings, there is no significant effect on Debt To Equity, Gross Profit Margin, Total Asset Turnover on changes in earnings. And together it cannot have a significant effect on changes in earnings.